Investigating secondary school Iraqi EFL classroom discipline behaviors in terms of applying communicative activities - Hassan, Assistant Instructor: Susan Abid (مجلة أبحاث الذكاء, 2019)
The present study aims at investigating secondary school Iraqi e f l classroom discipline behaviors in terms of applying communicative activities. An observation checklist has been adopted from the national education association (1999) and method to suite the Iraqi environment .a simple of 45 Iraqi e f l secondary school male and female teachers has been randomly selected to achieve the aim of the present study validity and reliability of the observation check list have been achieved. Data has been gathered and analyzed using suitable statistical tools. Results show that the behaviors stated in the checklist have been all employed by the sample of the present study.